Transatlantic genre hybridity in Danny Boyle's 28 Days Later. Issue 1 (1st April 2016) - Decker, Lindsey
This article examines the relationship between genre hybridity and national genres in British director Danny Boyle's financially successful and critically acclaimed horror film 28 Days Later (2002). The film narratively and visually cites American director George Romero's original Dead trilogy (1968's Night of the Living Dead, 1978's Dawn of the Dead and 1985's Day of the Dead), positioning itself within the zombie horror subgenre. However, much of the cinematography in 28 Days Later self-reflexively deploys cinematographic practices common in British documentary, realist film and heritage film. The film also responds to contemporary British cultural concerns, including animal activism, media effects and surveillance culture. Through its cinematography and relation to contemporary cultural issues, the film knowingly positions itself as part of British cinema. Through its generic hybridity and self-reflexivity, 28 Days Later engages with British film culture's discursive construction of British cinema and its transatlantic relationship with the US film industry, often represented metonymically by Hollywood. This article argues that in doing so, the film produces a subtle critique of Americanization, positioning the film as part of the anti-Americanization discourse prevalent in British film culture, as well as attempting to frame the horror genre as a worthy element of British national cinema.